The clash of pro and anti-protest sentiments during the Pandemic: Youths’ Narratives in Malaysia and Hong Kong as Contrasting political communication - Aqmal Afiq Shamsul Bahri,; Geetha Govindasamy,; Nur Shahadah Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic has had far-reaching effects, impacting not only the health and economic sectors but also the global political landscape. In response, certain youth groups have turned to protests as a means of expressing their dissatisfaction with their governments. This study aims to analyse the conflicting narratives between protest groups that support the right to assemble and the anti-protest narratives promoted by governments. While the Malaysian and Hong Kong governments implemented Movement Control Order and a national lockdown respectively, to curb the spread of the coronavirus, young people within these countries perceived these measures as incompatible with their political objectives. This study employs a narrative analysis approach and the theoretical framework of New Social Movement (NSM) in order to examine this issue. The findings of this study indicate the youths in Malaysia and Hong Kong who supported mobilizing protests during the pandemic perceive the government’s presented narratives and response as a defence mechanism to opportunistic suppression of democratic, government-critical actions. Thus, it can be concluded that there is a clear clash of implicit political messages conveyed by both the youths and governments, with the pandemic serving as the instigating factor in motivation for or against the mobilization of protests.